Development of beneficiation technique for bentonite for applications in petroleum industry - Irawan, Sonny (2006)
Bentonite from Andrassy and Mansuli area of Sabah had been proven containing higher impurity minerals than commercial bentonite used in petroleum industry. This study comprises an optimum beneficiation process to upgrade the quality of Sabah bentonite by removal of iron and quartz content from it. Several organic acids have been studied but only the oxalic acid can successfully be used. Oxalic acid can be produced by fermentation with filamentous fungi such as Aspergillus and Penicillium, using as substrate residues with high organic carbon content. The exhaust fermentation medium can be the extracting agent for dissolving the bentonite iron-oxides. This process is economically favourable; besides producing effluents which are easy to purify. Other parameters that included in this study are oxalic acid concentration, beneficiation time, temperature and pH. In general, the optimum conditions for Andrassy and Mansuli samples beneficiation process occurred at an oxalic acid concentration of 7.1 Kg m-3 with 2 hours beneficiation time, temperature at 80°C, and a pH less than 2. The results obtained after beneficiation indicated that the content of the montmorillonite mineral from Andrassy and Mansuli sample show improvement with increment from 47 % to 258 % of the original value. The maximum associated silica and iron oxide released with gravitational process are in the range of 2.51% to 11.92% and 1.38% to 13.33%, respectively. The Liquid limit, plastic limit and plasticity index improved varying from 89.82% to 229.63%, 0.40% to 37.13% and 181.78% to 582.57%, respectively. The moisture content and moisture absorption increased in the range of 9.92% to 63.33% and 3.42% to 79.26%, respectively. The cation exchange capacity improved in the range of 22.45 % to 58.54 % and the specific surface area increment from 17% to 104.50%. However, the upgraded sample failed to fulfil the API (American Petroleum Institute) requirements for rheological properties when used as a material in drilling mud and an additive for oilwell cement. Thereafter, certain polymer dispersant had been added to improve rheological properties of the upgraded Sabah bentonite slurry so that it can be used as a drilling mud material and as oilwell cement additive. The YP/PV ratio of the beneficiated samples with addition of 1% to 4% wt Tannathin successfully met the API 13A and 10A requirement. The fluid loss of the beneficiated sample reduced when 2% to 2.5% wt of Tannathin was added. Generally, the degree of improvement of bentonite quality mainly depend on the origin of bentonite itself, it’s composition, chemical used in the beneficiation process and it’s concentration, beneficiation time, temperature and pH of the solution